Time-lagged prediction of rainfall-runoff processes through black-box and regression techniques - Li, Siyu. (2012)
This paper focuses on the study of comparison among various black box and regression-based techniques in determining the rainfall-runoff relations. Without considering the temperature, topography or other parameters of the study area, simply using the data of rainfall and runoff to predict the future runoff is the key characteristic of these techniques. Ignoring the parameters of temperature, topography may lead to inaccuracy in forecasting future runoff, but the use of black-box or regression-based techniques provide a simple and fast way to determine the runoff.